Problems of the Novice Principal - Harvey B. Alvy; Theodore Coladarch (Journal of Research in Rural Education, 1985)
A taxonomy of major responsibility areas, component activities, and administrative processes was used as the framework for identifying problems encountered by novice principals. The population of 70 Montana elementary and secondary principals, completing their first or second year in the Spring of 1982, was mailed a questionnaire to identify problem areas with respect to (a) curriculum and instruction, (b) pupil personnel relations, (c) professional personnel relations, (d) school-community relations, (e) school-wide management, (f) financial management, (g) school-district collaboration, (h) facility management, and (i) administrative processes. Curriculum and instruction and professional personnel relations were found to be the two most difficult responsibility areas for novice principals. Further, novices spent considerably more of their time with professional and pupil personnel than in their preferred area of curriculum and instruction. Correlational analyses indicated a greater correspondence between actual versus ideal sources of help (r= .93) than between actual versus desired time priorities (r= .68). Novices hired from within the district and those with previous administrative experience reported more difficulty than novices hired from outside or those with no previous administrative experience. These results are discussed within the context of school effectiveness research.